Pelatihan Digital Marketing untuk Meningkatkan Omset Penjualan dan Pelatihan Pembuatan Label Kemasan menggunakan Canva - Alawiah, Enok Tuti; Setyorini, Dini; Hasanudin (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The Tajur Halang Makmur UMKM Cooperative has good potential but has not been supported by the abilities of its members. The problems faced by partners are in the field of product production and marketing. The solution is to provide training on making attractive packaging label designs using the Canva application and digital marketing training to increase partners' sales turnover. The activity method is carried out offline and results in increased partners' abilities and skills in terms of digital marketing to expand sales reach and skills in mastering the Canva application to design attractive packaging for the products produced